2008
DOI: 10.1139/g08-009
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization, genetic analysis, and molecular mapping of a new mutant gene for male sterility in rice

Abstract: xs1 is a male-sterile rice mutant derived from a spontaneous mutation. The floret of the mutant, consisting of 6 stamens and 1 pistil, looks the same as that of the wild type except that the filaments are long and thin and the anthers are withered in white transparence. It is confirmed that xs1 is a no-pollen type of male-sterile mutant, for no pollen grains can be stained with I(2)-KI solution and the anther locules are always hollow. Anther transverse sections indicate that the mutant microspores are abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We have previously identified an allelic mutant of eat1 , namely eat1‐5 , in the background of Minghui63 ( indica rice) by employing a map‐based cloning approach (Chu et al., 2010; Zuo et al., 2008; Figure S14). The eat1‐5 microspores were abnormally collapsed and degraded, and failed to form functional pollen grains, mimicking the defect phenotypes of eat1 reported by Ji et al.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously identified an allelic mutant of eat1 , namely eat1‐5 , in the background of Minghui63 ( indica rice) by employing a map‐based cloning approach (Chu et al., 2010; Zuo et al., 2008; Figure S14). The eat1‐5 microspores were abnormally collapsed and degraded, and failed to form functional pollen grains, mimicking the defect phenotypes of eat1 reported by Ji et al.…”
Section: Resultsmentioning
confidence: 99%
“…Floral structures of the mutant and wild-type plant were observed under an optical microscope before flowering. Pollen fertility was investigated after staining with 1% I2-KI solution [23]. Anthers of the florets were placed on slides with I2-KI solution and nipped into pieces with forceps to spill out pollen grains.…”
Section: Anatomic and Paraffin Sectionmentioning
confidence: 99%
“…The total rice genomic DNA was isolated according to the method of Wang and Fang [28] and Zuo et al [23] with modifications. Powdered rice leaves were first incubated with the extraction buffer (100 mM Tris-Cl; 50 mM EDTA; 500 mM NaCl; 1.5% SDS; pH 8.0) at 65˚C, and then phenol-chloroform extraction and alcohol precipitation were performed.…”
Section: Dna Extraction and Pcr (Polymerase Chain Reaction) Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the keyword 'salt tolerance' was mapped to the sodium ion transmembrane transporter gene AT4G10310, and Os01g0307500 was suggested as a homologue of AT4G10310. Using a no-pollen type of male-sterile mutant (xs1), Zuo et al (2008) revealed that mutant microspores are abnormally condensed and agglomerated to form a deeply stained cluster at the late microspore stage. This halts the microspore vacuolation process, and therefore, the mutant forms lack functional pollen.…”
Section: In Silico Positional Cloning After Qtl Analysis In Ricementioning
confidence: 99%